Attitudes towards ambiguous information and stock returns - Ziyun Zhang (Cogent Economics & Finance, 2019)
This study examines whether investors' attitudes toward ambiguity can explain cross-sectional stock returns by investigating the relationship between future stock returns and option-implied volatilities as well as implied third moments. We find that investors' attitudes toward different levels of ambiguous stocks help explain cross-sectional variations of stock returns during the 1996-2010 period in the U.S. stock market. In this study, investors' attitudes toward ambiguity are measured by stocks' option-implied third moments. Negative-skewed quintiles represent ambiguity aversion and vice versa. Different levels of ambiguity for stocks are distinguished by stocks' option-implied volatility. High volatility quintiles represent stocks with high information ambiguity. Independent two-dimension sorting results show that ambiguity averters are compensated for holding stocks with higher ambiguity. Meanwhile, ambiguity-loving investors are willing to give up some returns to hold stocks with lower levels of ambiguity. The results show that both types of ambiguity attitudes increase the factor model's explanatory power. The estimated monthly premiums for ambiguity-aversion and ambiguity-loving factors are 0.38% and 1.28%, respectively.
Keywords: G12; 330; uncertainty; ambiguity-aversion premium; ambiguity-loving premium; stock returns; factor model